Estudo da influência do epítopo c-Myc na formação da interface entre o SCFV e o CD19 para aplicação em CAR - Lima, Ana Júlia Ferreira (2022)
Chimeric Antigen Receptors (CARs) are recombinant proteins constructed to be expressed on the T lymphocyte's surface to redirect these cells' action against target cells. The CD19 membrane protein is an important immunotherapies target for the B-cell cancers treatment based on the CARs use, as it is overexpressed in these cells. Protein epitopes can be used as protein markers (tags) to facilitate detection and purification experiments. The CAR general structure has in its extracellular domain a recognition domain responsible for interacting in a specific way with the target molecule. This domain is usually composed of a single-chain variable antibody fragment (scFv). In the Kymriah anti-CD19 CAR, the scFv used is derived from the murine antibody FMC63, where a tag, such as the c-Myc tag, can be added to assist in experimental procedures such as those mentioned above. However, because scFv is the domain that directly interacts with CD19, it is necessary to assess whether this tag addition affects the scFv and CD19 interface formation. This project aims to evaluate, through Molecular Dynamics (MD) simulation, whether the c-Myc tag addition affects the scFv structural stability and the interaction between scFv and CD19. The scFv structures (with and without c-Myc) and CD19 were modeled and submitted to DM simulation. It was observed that the c-Myc tag presence did not affect the scFv structure, confirmed by the low root mean square deviation (RMSD) with the maintenance of the scFv structures (with and without c-Myc). However, a negative Intermolecular Interaction Potential was observed (IIP) between c-Myc and scFvs CDRs, indicating that attractive interactions occur between the structures resulting from approximations that can affect the interface formation. DM simulations with the scFv (with and without Myc) interfacing with CD19 were performed (c-Myc-scFv-CD19 and scFv-CD19) in triplicate (S1, S2, and S3), and in a long-time of 1000 ns. The RMSD curves show similar profiles between the simulations, demonstrating that there is no structural change in scFv and CD19, regardless of the c-Myc presence. The IIP profile shows negative energy throughout the simulation, demonstrating that there is an attractive interaction with and without c-Myc. Thus, it can be concluded that the c-Myc tag presence to the scFv does not affect its structural balance. However, depending on the c-Myc position concerning the CDRs, it can affect the interface formation and consequently the interaction between the scFv and the CD19.